Tourism crisis management: The mindful learning from tourism crises - Ghaderi, Zahed; Mat Som, Ahmad Puad (2013)
The mindful learning demonstrates how, if barriers are overcome, learning can contribute to effective crisis management through not only mitigating the negative effects but also potentially averting a crisis from occurring. This paper is an attempt to examine how tourism organizations can mindfully learn from crises and disasters and encourage the adoption of a mindful culture in their organizations. The results show that there are many barriers which impede organizations to learn mindfully and adjust themselves to the new situations. It also discusses that most tourism organizations neglected mindful organizational learning and paid more attention to superficial or single loop learning from tourism crises.